Pragmatic Markers in Eugene O’Neill’s Ile: Discourse Coherence Relations (Universitas Islam Negeri Sunan Ampel Surabaya, 2015)
This study aimed to investigate the types of pragmatic markers in a drama entitled Ile. The study is based on Fraser’s theories of pragmatic markers and discourse coherence relations. This research employs a descriptive qualitative research method since the presentation of the results of the analysis is in the form of tabulation and description of the data. The present study employs one of those three kinds of triangulation suggested by Miles and Huberman that is expert triangulation. The results of the analysis of the data indicate that from 4,369 words in the drama, 415 linguistic items are identified as pragmatic markers which are distributed into four major types of pragmatic markers: basic markers (159 items), commentary markers (5 items), parallel markers (121 items), and discourse markers (130 items). Coherence relations which are found in drama Ile shows that those pragmatic markers provide the bridge between the propositional parts of the discourse that making it possible for the characters in drama to move quickly and smoothly from one topic to another